Josephson current suppression in three-dimensional focused-ion-beam fabricated sub-micron intrinsic junctions - Warburton, P; Fenton, J; Korsah, M; Grovenor, C (2006)
We have fabricated intrinsic Josephson junction arrays in Tl2Ba2CaCu2O8 thin films using three-dimensional focused-ion-beam milling. We have measured the dependence of the switching current density of these arrays at 4.2 K upon the junction cross-sectional area. There is strong suppression of the switching current density for junctions of area less than 1 mu m(2), the current extrapolating to zero at an area of 0.25 mu m(2). We discuss the possible roles of gallium ion implantation and both thermal and quantum fluctuations in this current suppression.